The genetic basis for most patients with pustular skin disease remains elusive. (1st March 2018) - Mössner, R.; Wilsmann‐Theis, D.; Oji, V.; Gkogkolou, P.; Löhr, S.; Schulz, P.; Körber, A.; Prinz, J.C.; Renner, R.; Schäkel, K.; Vogelsang, L.; Peters, K.‐P.; et al.
Summary: Background: Rare variants in the genes IL36RN, CARD14 and AP1S3 have been identified to cause or contribute to pustular skin diseases, primarily generalized pustular psoriasis (GPP). Objectives: To better understand the disease relevance of these genes, we screened our cohorts of patients with pustular skin diseases [primarily GPP and palmoplantar pustular psoriasis (PPP)] for coding changes in these three genes. Carriers of single heterozygous IL36RN mutations were screened for a second mutation in IL36RN . Methods: Coding exons of IL36RN, CARD14 and AP1S3 were sequenced in 67 patients – 61 with GPP, two with acute generalized exanthematous pustulosis and four with acrodermatitis continua of Hallopeau. We screened IL36RN and AP1S3 for intragenic copy‐number variants and 258 patients with PPP for coding changes in AP1S3 . Eleven heterozygous IL36RN mutations carriers were analysed for a second noncoding IL36RN mutation. Genotype–phenotype correlations in carriers/noncarriers of IL36RN mutations were assessed within the GPP cohort. Results: The majority of patients (GPP, 64%) did not carry rare variants in any of the three genes. Biallelic and monoallelic IL36RN mutations were identified in 15 and five patients with GPP, respectively. Noncoding rare IL36RN variants were not identified in heterozygous carriers. The only significant genotype–phenotype correlation observed for IL36RN mutation carriers was early age at disease onset. Additional rare CARD14 or AP1S3 variants were identified in 15% of IL36RN mutation carriers. Conclusions: The identification of IL36RN mutation carriers harbouring additional rare variants in CARD14 or AP1S3 indicates a more complex mode of inheritance of pustular psoriasis. Our results suggest that, in heterozygous IL36RN mutation carriers, there are additional disease‐causing genetic factors outside IL36RN .